Fire resistance of a prefabricated bushfire bunker using aerated concrete panels. (20th June 2018) - Nguyen, Q.T.; Ngo, T.; Tran, P.; Mendis, P.; Aye, L.; Baduge, S. Kristombu
Highlights: Full-scale fire testings of 3 m × 3 m PLAC panels are conducted. A 125, 000 elements model is developed to simulate fire performance of PLAC panels. A dual-skin PLAC fire bunker is concluded to ensure fire safety compliance. Super light PLAC panels of 500 kg/m 3 is required in severe bush fire conditions. Abstract: Prefabricated lightweight aerated concrete (PLAC) panels provide low thermal conductivity, potentially high stiffness-to-weight ratios, cost-effective material and structural systems and rapid modular construction. These panels can be utilised as floor slabs or external walls for various applications in building construction. The fire performance of the PLAC panel is examined in this work for a particular case, namely a prefabricated emergency bushfire shelter, which is one of the key applications of PLAC panels. Since, bushfires have unique heating curves, standardised tests are not useful and the system needs to be tested in a manner such that the heat flux of an actual bush fire can be reproduced. In this study, the fire performance enhancement of dual-skin bushfire bunkers, which are comprised of lightweight concrete and base metal thickness (BMT) steel, are examined experimentally and validated numerically. The Speedpanel PLAC modular panel explored in this work is a lightweight wall system primarily used for acoustic and thermal insulation purposes. Burning experimental studies of a single panel and dual-skin bunkers are carried out on a full scale. The experimental results are compared with fire safety codes for building materials to identify the key areas for improvements. A fire dynamic numerical model has been developed in this work using the Fire Dynamics Simulator (FDS) to simulate the burning process of PLAC structures. Numerical results of heat production are presented in comparison with experimental observations for validating the computational model. The proposed numerical model is used to predict the fire performance of a dual-skin bushfire bunker, demonstrating the need to have at least two PLAC layers to ensure fire safety compliance.